Insights into the functional mechanisms of three terpene synthases from Lavandula angustifolia (Lavender) - Liu, Dafeng; Song, Hongying; Deng, Huashui; Abdiriyim, Ablikim; Zhang, Lvxia; Jiao, Ziwei; Li, Xueru; Liu, Lu; Bai, Shuangqin (Frontiers in Plant Science, 2024)
Lavender species are of significant economic value, being cultivated extensively worldwide for their essential oils (EOs), which include terpenes that play crucial roles in the cosmetic, personal care, and pharmaceutical industries. The terpene synthases in lavender, such as Lavandula angustifolia linalool synthase (LaLINS), limonene synthase (LaLIMS), and bergamotene synthase (LaBERS), are key enzymes in terpene biosynthesis. However, the functional mechanisms underlying these enzymes remain poorly understood. Here, we used AlphaFold2 to predict the three-dimensional structures of LaLINS, LaLIMS, and LaBERS. The hydrodynamic radius of LaLINS, LaLIMS and LaBERS were 5.7 ± 0.2 nm, 6.2 ± 0.3 nm, and 5.4 ± 0.2 nm, respectively. Mutations D320A or D324A led to a complete loss of activity in LaLINS compared to the wild-type (WT) enzyme; similarly, mutations D356A or D360A abolished activity in LaLIMS, and D291A or D295A eliminated activity in LaBERS. Furthermore, the genes LaLINS, LaLIMS, and LaBERS exhibited significantly higher expression levels 2/22